1988
DOI: 10.1159/000195423
|View full text |Cite
|
Sign up to set email alerts
|

Early Bronchodilating Effect of a New Oral Beta-2-Receptor Agonist (Broxaterol) in Bronchial Asthma

Abstract: In order to determine the bronchodilating activity and safety of two beta-2-receptor agonists, broxaterol and procaterol, compared with a placebo, 12 patients with reversible airway obstruction were tested in a double-blind cross-over study. The drugs were administered orally and the dosage of broxaterol was 0.5 mg, that of procaterol 0.05 mg.Measurements of forced expiratory volume in 1 s (FEV1), heart rate and blood pressure were performed before and 30, 60, 120, 240, 360, and 480 min after each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The onset of action of broxaterol was seen at 30 min, which was more rapid than for procaterol. Peak effect was reached at 120 min for both drugs, and an unusual persistence of bronchodilation, when compared to placebo, lasted up to 8 h. No study has shown a longer-lasting effect of oral broxaterol than that reported by Chetta et al [7].…”
Section: Oral Tablet Studiesmentioning
confidence: 66%
See 2 more Smart Citations
“…The onset of action of broxaterol was seen at 30 min, which was more rapid than for procaterol. Peak effect was reached at 120 min for both drugs, and an unusual persistence of bronchodilation, when compared to placebo, lasted up to 8 h. No study has shown a longer-lasting effect of oral broxaterol than that reported by Chetta et al [7].…”
Section: Oral Tablet Studiesmentioning
confidence: 66%
“…Minette and Prihadi [13] reported an increase in heart rate of 4-8 beats/min and in systolic blood pressure of up to 10 mm Hg lasting several hours. These effects were greater than those produced by salbutamol 4 mg. Chetta et al [7] reported a slight increase in heart rate 30-120 min after both broxa terol and procaterol.…”
Section: Cardiovascular Effectsmentioning
confidence: 97%
See 1 more Smart Citation